Improvement of Photovoltaic Cell Efficiency by Using Water Mist to Reduce Photovoltaic Cell Temperature - ภู่ทอง, สิทธิพัฒน์; วิมานจันทร์, วิชาญ; จันทวงษ์, ปรีดา; เมืองลือ, เฉลิมพล (Journal of Energy and Environment Technology of Graduate School Siam Technology College, 2018)
Temperature factor significantly affected on the electrical production of photovoltaic (PV) cell. Every one degree Celsius (oC) temperature rise corresponds to a drop in efficiency by 0.5%. The aim of this project is to reduce the operating temperature by using water mist to increase the efficiency of PV cell. The study setup consisted of two 50 Watt Monocrystalline PV cell, tilt of 15 degree with reference to the horizontal. One is the control, another is the experiment that equipped with sprayer to spray water mist directly to the back surface of PV cell. The experiments were performed at the same time, same place. Electrical current, voltage, solar radiation, ambient temperature, relative humidity and both surfaces temperature of PV cell were recorded and compared.The results show that using water mist spray can reduce temperature 19.9 oC on front surface and 24.9 oC on back surface of PV cell. As a consequence, the electrical efficiency is increased by 13.788 % at the peak solar radiation condition (Solar intensity >1000 W/m2). Water consumption rate is only 11.914 L/h.